1990
DOI: 10.1007/bf01786885
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cytotoxicity and interleukin 1 production of blood monocytes of lung cancer patients

Abstract: The effects of lung cancer on the abilities of blood monocytes to produce interleukin-1 and to mediate antitumor activity were examined. The functional integrity of blood monocytes was determined by their capacity to respond in vitro to a variety of activating agents and become tumoricidal, as assessed by a radioactive release assay and ability to produce interleukin-1 in vitro. The results show that the presence of lung cancer significantly increased the number of harvested blood monocytes and that the sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The production of IL-1 and TNF in cancer patients has been reported to be defective in some cancers [11,15,31] as well as comparable or increased in others [1,13,28,29]. According to our results (Table 1), unstimulated monocytes from patients of both the groups showed a slightly higher level of IL-1 activity than normal donors which was not found to be significant.…”
Section: Inhibition Of Monocyte Cytotoxicity By Monoclonal Antibody Tcontrasting
confidence: 68%
“…The production of IL-1 and TNF in cancer patients has been reported to be defective in some cancers [11,15,31] as well as comparable or increased in others [1,13,28,29]. According to our results (Table 1), unstimulated monocytes from patients of both the groups showed a slightly higher level of IL-1 activity than normal donors which was not found to be significant.…”
Section: Inhibition Of Monocyte Cytotoxicity By Monoclonal Antibody Tcontrasting
confidence: 68%
“…In vitro-treated human monocytes killed allogeneic and autologous tumors (including melanoma, ovarian, colon, and renal carcinoma [7,[18][19][20]), but had no by-stander toxicity towards normal cells, even when mixed with the tumor targets [4,21]. Importantly, several of these studies showed that monocytes from cancer patients could be activated to similar levels of tumoricidal activity as cells from healthy donors [7,[18][19][20].…”
Section: Preclinical Studies and Animal Trialsmentioning
confidence: 98%
“…Our study confirmed that NK cells played a major role in the mechanism of anti-tumor activity of anti-HM1.24 mAb. Although NK activity is quite important for host defense against cancers, decreased NK activity [25,26] and monocyte functions [27,28] were reported in lung cancer patients. In our study, NK activity in patients with lung cancer tended to be reduced as compared with that in healthy donors, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%